Benefit or Harm? A Study on Impact of Collusion on the Quality of Life among Palliative Care Patients - Victor, Anju (Indian J Palliat Care, 2018)
BACKGROUND: In India, roughly one-half of patients undergoing cancer treatment are unaware of their diagnosis or treatment. The intention of this study is to determine the prevalence of collusion and its influence on quality of life (QOL) among patients in palliative care settings. METHODOLOGY: A cross-sectional study was conducted among 100 palliative care patients to assess the extent of knowledge about their diagnosis and prognosis. The caretakers and the treating doctors were interviewed using a semi-structured questionnaire to assess if diagnosis was revealed to a patient. QOL of the patients was assessed using the European Organisation for Research and Treatment of Cancer QOL Questionnaire-C30 questionnaire. RESULTS: The prevalence of collusion was 37%, i.e., in more than one-third of the palliative care patients; caregivers restrained doctors from disclosing the diagnosis. The prevalence of collusion was less among patients with higher educational qualification (P = 0.027) and professionals (P = 0.025). Collusion was not associated with gender, type of family, place of residence, and socioeconomic status (SES). In multivariate regression, collusion (odds ratio = 10.53) was independently associated with poor QOL when adjusted for age, gender, place of residence, religion, educational status, family type, and SES. CONCLUSION: Collusion is fairly prevalent and it worsens the QOL among cancer patients. Since the main driver for collusion is the strong desire among caregivers to protect the physical and psychological well-being, the findings of the study could motivate the caregiver for a more open and honest communication.